The impact of knowledge sharing on organizational learning and effectiveness - Yang, Jen-te (Journal of knowledge management, 2007)
Purpose - The purpose of this study is to empirically investigate the extent to which knowledge sharing and organizational learning affect organizational effectiveness.Design methodology approach - The research samples have been drawn from all levels of employees in the organizational hierarchy of international tourist hotels in Taiwan. The questionnaires were distributed to 1,200 participants across nine international tourist hotels in Taiwan. These hotels are globally managed or franchised by international groups of hotels and resorts.Findings - Of 499 usable questionnaires, the results suggest that knowledge sharing would facilitate the transformation of collective individual knowledge to organizational knowledge without the existence of orphaned knowledge and knowledge depreciation. Furthermore, this would result in the advancement of organizational learning and eventually, the enrichment of organizational effectiveness.Practical implications - The more individual intellectual capital is transferred to organizational assets, the greater the degree of strength of organizational capabilities will become. If organizations do not implant mechanisms for storing that all employees collectively learn, effects are not enduring. There would furthermore be a limited contribution to organizational learning.Originality value - This study contributes to KM literature that suffers from a paucity of research on the empirical examination of this subject.